Outcome-based commissioning of knee arthroplasty in the NHS: system error in a national monitoring programme and the unintended consequences on achieving the Best Practice Tariff. (December 2018) - Middleton, R.; Wilson, H. A.; Alvand, A.; Abram, S. G. F.; Bottomley, N.; Jackson, W.; Price, A.
Abstract : Aims: Our unit was identified as a negative outlier in the national patient-reported outcome measures (PROMs) programme, which has significant funding implications. As a centre that carries out a high volume of unicompartmental knee arthroplasty (UKA), our objectives were: 1) to determine whether the PROMs programme included primary UKA when calculating the gain in Oxford Knee Score (OKS); and 2) to determine the impact of excluding primary UKA on calculated OKS gains for primary knee arthroplasty. Materials and Methods: National PROMs data from England (2012 to 2016) were analyzed. Inclusion of UKA cases in the national PROMs programme was determined using clinical codes. Local OKS gain was calculated for UKA and TKA and compared with the published PROMs results for 2012/13. Results: Use of the recommended codes for primary UKA excluded 99.6% of UKAs locally and 97% nationally from PROMs programme analysis. Inclusion of primary UKAs in PROMs analysis improved our OKS gain from 15.1 (below average) to 16.3 (above average) for 2012/13 for primary knee arthroplasty. Conclusion: Exclusion of UKA patients from the PROMs programme is a nationwide issue that potentially introduces bias when comparing OKS gain between centres. Where commissioning decisions are based on routinely collected data, it is imperative that the underlying methodology is appropriate to generate valid results.